2002
DOI: 10.1176/appi.ajp.159.8.1315
|View full text |Cite
|
Sign up to set email alerts
|

Axis I and II Psychiatric Disorders After Traumatic Brain Injury: A 30-Year Follow-Up Study

Abstract: The results suggest that traumatic brain injury may cause decades-lasting vulnerability to psychiatric illness in some individuals. Traumatic brain injury seems to make patients particularly susceptible to depressive episodes, delusional disorder, and personality disturbances. The high rate of psychiatric disorders found in this study emphasizes the importance of psychiatric follow-up after traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
235
3
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(257 citation statements)
references
References 31 publications
5
235
3
9
Order By: Relevance
“…In addition to the changes in cognition, behavior, and personality described above, a significant body of evidence suggests that TBI results in an increased relative risk of developing various psychiatric disorders, including mood and anxiety disorders, substance abuse and psychotic syndromes (73)(74)(75)(76). For example, Kopenen et al (76) studied 60 individuals 30 years after their TBI and found that almost half (48%) developed a new Axis I psychiatric disorder after their injury.…”
Section: Relationship Of Tbi To Psychiatric Disordersmentioning
confidence: 99%
“…In addition to the changes in cognition, behavior, and personality described above, a significant body of evidence suggests that TBI results in an increased relative risk of developing various psychiatric disorders, including mood and anxiety disorders, substance abuse and psychotic syndromes (73)(74)(75)(76). For example, Kopenen et al (76) studied 60 individuals 30 years after their TBI and found that almost half (48%) developed a new Axis I psychiatric disorder after their injury.…”
Section: Relationship Of Tbi To Psychiatric Disordersmentioning
confidence: 99%
“…Anxiety disorders are common comorbidities associated with traumatic brain injury (TBI) [1][2][3]. As defined by the Centers for Disease Control and Prevention, anxiety disorders have an aggregate 12 month prevalence of 10% among the general population [4].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, about 1.1% of the US population is living with long-term disability as a result of TBI [1], which often includes psychiatric disorders, most commonly depression [2]. Although the risk for developing Major Depressive Disorder (MDD) is significant in the first year after TBI [3], an elevated risk for depression persists across the lifespan.…”
Section: Introductionmentioning
confidence: 99%